Keberadaan Spesies Serangga pada Berbagai Pertanaman Sayuran Tumpang Sari : Studi Kasus di Desa Talang Pasai Kecamatan Pagar Alam Utara Kota Pagar Alam Sumatera Selatan - Pujiastuti, Yulia; Andini Siregar, Regina Sri; Anggarini, Dewi; Munandar, Rudi Putra; Ayu Wandhari, Vindha (Seminar Nasional Lahan Suboptimal, 2018)
Pujiastuti et al, 2019.The Existence of Insect Species in Various Intercropping Vegetable Crops: Case Study in Talang Pasai Village, Pagar Alam Utara District, Pagar Alam City South Sumatra. pp. 103-109.Intercropping plants are a cropping system that is widely applied by farmers ie planting more than one species of plant. In addition to increasing crop production, intercropping systems are also optimize land functions. Intercropping systems are also wellknown to affect the diversity of insects that live or visit plants. The aim of the study was to identify insects  living on plants or around plants and their role in intercropping systems. Research had been carried out in the highlands in the North Pagar Alam District, Pagar Alam City, South Sumatra, in July-August 2018. Insect observation methods were conducted by direct observation and hand picking. Observations were carried out 3 times with 1 week observation interval. The types of intercropping observed included red onions, chili-celery, chili-cabbage and eggplant-carrots. The results of observations on plants intercropping in which  chili plants as one of the crop showed chili plants were more visited, seized or attacked by insects compared to their partner plants. In the chili-red onion plants, it was  found 4 orders, 5 families and 6 species, in chili-celery plants found 4 orders, 5 families and 10 species, in chili-cabbage plants found 5 orders, 6 families and 8 species, whereas in the eggplant-carrot plants found 5 orders, 11 families and 13 species. Intercropping with chili plants shows that their partner plants are less attacked by pests.